Cannabidiol Reduces Inflammatory Lung Damage After Meconium Aspiration in Newborn Piglets - Arruza, Luis; Barata, Lorena; Vierge, Eva; Rodríguez, Maria José; Del Pozo, Aaron; Hind, William; Martínez-Orgado, José (Frontiers in Pediatrics, 2022)
Aim: To assess the effects of cannabidiol (CBD) on lung damage in a piglet model of meconium aspiration syndrome (MAS). Methods: MAS was modelled in newborn piglets via intratracheal instillation of 20% meconium in saline collected from healthy newborn humans. Piglets were treated i.v. with 5 mg/kg CBD (MAS+CBD) or Vehicle (MAS+VEH) 30 minutes after MAS induction and monitored for 6 h. Ventilated piglets without meconium instillation served as controls (CTL). Ventilatory and haemodynamic monitoring, histological and biochemical studies assessed the effects of treatment. Results: Post-insult administration of CBD reduced MAS-induced deterioration of gas exchange, improving respiratory acidosis (final pH 7.38±0.02, 7.22±0.03 and 7.33±0.03 and final pCO2 39.8±1.3, 60.4±3.8 and 45.7±3.1 mmHg for CTL, MAS+VEH and MAS+CBD, respectively, p<0.05). These beneficial effects were obtained despite the less aggressive ventilatory settings required for CBD-treated animals (final Minute Volume 230±30, 348±33 and 253±24 mL/kg/min and final Oxygenation Index 1.64±0.04, 12.57±3.10 and 7.42±2.07 mmHg for CTL, MAS+VEH and MAS+CBD, respectively, p<0.05). CBD’s beneficial effects on gas exchange were associated with reduced histological lung damage, reduced leucocyte infiltration and oedema (Histopathological score 1.6±0.3, 8.6±1.4 and 4.6±0.7 points for CTL, MAS+VEH and MAS+CBD, respectively, p<0.05), as well as reduced TNFα production (0.04±0.01, 0.34±0.06 and 0.12±0.02 A.U. for CTL, MAS+VEH and MAS+CBD, respectively, p<0.05). Moreover, CBD improved blood pressure stability (final mean blood pressure 74.5±0.2, 62.2±6.2 and 78.67±4.1 mmHg for CTL, MAS+VEH and MAS+CBD, respectively, p<0.05). Conclusion: CBD reduces histologic lung damage and inflammation in a piglet model of MAS. This translates into improved gas exchange and blood pressure stability.